Learning Object as an Educational Innovation Tool for Energy Management Systems Teaching Based on the ISO-50001 Framework: An Interdisciplinary Descriptive Approach - López-Leyva, Josué Aarón; Mellink-Méndez, Sialia Karina; Murillo-Aviña, Gloria Janeth; Cañedo-Bobadilla, Paola Monet (My University, 2023)
Formal sustainability teaching at all educational levels is imperative for the development of humanity. Particularly, energy resources management is a significant part of sustainability in society and companies. In this way, the problem related to energy management based on international standards currently persists in both academic and labor scenarios. Thus, students do not achieve the learning outcomes related to this topic during their academic life, which in a certain way, hinders student success when they graduate from school. As a support to this situation, this article shows the theoretical proposal of a learning object for the ISO-50001 standard from an interdisciplinary descriptive perspective, i.e., engineering sciences, graphic design (Transition Design as a transdisciplinary approach), management, and education sciences, among other disciplines, contribute to this project. As a final result, the opportunities and challenges of designing and developing a potential learning object that permits improving the efficiency of the learning outcomes related to sustainability are discussed
Proceeding TEEM 2022: Thent International Conference on tecnologycal Ecosistems for Enhancing Multiculturality
Keywords: learning Object; Energy management; interdiciplinary; Blooms taxonomy; Campus Ensenada